Peran Rasa Syukur dalam Meningkatkan Kesejahteraan Psikologis Tenaga Kesehatan di Masa Krisis - Novi Elisadevi; Sulastri, Teraika Sri; Dasi, Irma; Utami, Nugraheni Putri (JURNAL RISET RUMPUN ILMU KESEHATAN, 2025)
This study aims to examine the role of gratitude in enhancing the psychological well-being of healthcare workers during times of crisis, particularly within the context of the COVID-19 pandemic. Using a qualitative approach through literature review and thematic analysis, the study finds that gratitude positively contributes to aspects of psychological well-being such as self-acceptance, life purpose, personal growth, and positive relationships with others. Gratitude also functions as an adaptive coping mechanism that strengthens the mental resilience of healthcare workers in facing work-related stress and high emotional risks. These findings highlight the importance of gratitude-based psychological interventions to support the mental health of healthcare professionals during crises.